Antioxidant, lipid peroxidation and cell membrane stability influence yield in Cucumis sativus L. by chitosan application under different sowing times - Ali, Mujahid; Ayyub, Chaudhary Muhammad; Silverman, Emily; Hussain, Zahoor; Iqbal, Shahid; Ayyub, Saqib; Akram, Bilal (Journal of Pure and Applied Agriculture, 2023)
Heat stress in a major obstacle in cucumber production in the Punjab province of Pakistan. To save cucumber production from heat stress, a study was designed to evaluate chitosan on cucumber genotypes for yield enhancement under three sowing dates. Four cucumber genotypes, two tolerant (L3466 and Desicucumber) and two susceptible (Suyo Long and Poinsett), were screened in a previous experiment under field conditions during 2016. The 1st sowing date was 15th March, followed by 1st April, and 15th April, respectively with four replications. Chitosan level (200 ppm) was applied as foliar spray at 30 days post-sow and then applied two times after a week interval. During present research, the highest summer temperature was 47.5 °C recorded in May, 48°C in June, and 46.1°C in July. Chitosan improved the enzymatic antioxidants and osmolytes in enhancing the ability of cucumber to tolerate heat stress. Enhancement in biochemical characteristics (Superoxide dismutase, peroxidase, catalase, and protein content) were observed in chitosan treated plants as compared with nontreated plants. It was revealed that yield per plant was highest in L3466 (2.12 kg) and Desi-cucumber (2.10 kg) with chitosan application on the 1st sowing date, while yield per plant was reduced in Suyo Long (0.31 kg) and Poinsett (0.29 kg) on the third sowing date with chitosan application. However, in 3rd sowing date Suyo Long and Poinsett could not survive at the fruiting stage without the chitosan application. L3466 and Desi-cucumber could be a benefit to farmers with chitosan application and breeders for further studies for heat stress tolerance. © 2020 Department of Agricultural Sciences, AIOU